Batasan Perlindungan Hukum Aktivis Lingkungan Hidup Dalam Tindak Pidana Ujaran Kebencian Di Media Sosial (Studi Kasus Putusan Nomor 374/Pid.Sus/2024/PT.SMG) - Achsia, El Aisna Putri; Wulan, Evi Retno (CV. Ulil Albab Corp, 2025)
This legal study examines the limits of legal protection for environmental activists in the context of hate speech offenses committed on social media, using Decision number 374/Pid.Sus/2024 / PN.SMG as a case study. This study examines the consistency of the judge's consideration in the decision with Article 66 of law no. 32 of 2009 on Environmental Protection and management (PPLH), which regulates the protection of environmental activists. The findings of the study indicate that, although the ruling excludes environmental activists, there are ambiguities in the implementation of Article 66 of the PPLH law, especially in terms of definitions and requirements for environmental activists, as well as the limits of legal protection provided. This study recommends broader regulation under Article 66 of the PPLH law to provide legal clarity and more complete protection for environmental activists while preventing potential abuse of the law. In addition, the study underscores the need for a balance between freedom of expression and protection against hate speech in the context of environmental advocacy.